PREVALENCE OF GLUTAMATE CARBOXYPEPTIDASE II C1561T, REDUCED FOLATE CARRIER 1 A80G, AND METHIONINE SYNTHASE A2756G GENE POLYMORPHISMS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AMONG SOUTH INDIANS - NITHYA K; ANGELINE T; PRISCILLA AS; ASIRVATHAM AJ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Glutamate carboxypeptidase II (GCPII), reduced folate carrier 1 (RFC1), and methionine synthase (MTR) genes involved in the folate metabolic pathway may play a key role in the pathogenesis of diabetes and its complications. The present study aimed to investigate the prevalence of genetic polymorphisms of GCPII C1561T, RFC1 A80G, and MTR A2756G in individuals with type 2 diabetes mellitus (T2DM) among South Indians. Methods: The study subjects consisted of 100 healthy individuals and 200 patients with T2DM. Genetic polymorphisms (GCPII C1561T, RFCI A80G, and MTR A2756G) in the folate metabolic pathway were analyzed by polymerase chain reaction-restriction fragment length polymorphism method. Statistical analysis was performed to test the level of significance. Results: With regard to GCPII C1561T and MTR A2756G gene polymorphisms, significant differences were not found when diabetic patients (with and without complications) and controls were compared according to different statistical models (dominant, recessive, and overdominant) p>0.05. A case–control genetic association analysis of RFC1 A80G gene polymorphism has shown that there was 3.7-fold increased risk for patients without complications and 4.9-fold increased risk for diabetic patients with complications. Conclusions: Our findings suggest that the GCPII C1561T and MTR A2756G gene polymorphisms were not significantly associated with diabetes and its complications. Whereas, the RFCI A80G gene polymorphism involved in folate metabolism confers increased risk for diabetes and its complications in South Indian population.